Development of Assessment Applications to Assist in Compilation of Guidance and Programs Counseling in Schools: A Systematic Review - Endang Santika (Business Finance Analyst Co., 2023)
The number of implementation of guidance and counseling services in schools carried out by Guidance and counseling teachers are not based on the results of a needs analysis student assessment, this makes the implementation of guidance and counseling services lacking clear goals. The development of technology and information has been very developed in the world education, especially guidance and counseling. Implementation of assessment to students already This can be done with the help of technological developments, one of which is the application. Study This aims to find out some of the development of assessment applications for students who has implications for the preparation of guidance and counseling programs by guidance and counseling teachers counseling. This study uses a systematic review method. The research results show Some of the student assessment applications in the preparation of guidance and counseling programs are AKPD, AUM, an application based on Visual Basic desktop software version 6 of this application was designed based on student independence competency standards (SKKPD) in SMA, using Short Message Service (SMS), a simple application that will help BK teachers in compile and plan the BK program based on the results of the assessment which is automatically compiled become a BK Service program that is in accordance with the HOTS 2013 Curriculum and 21st Century thinking, this is inspired by IKMS Paramitra, and assessment with Utilize the application from Google Forms.